Presence of same-sex kin promotes explorative behavior in subadult cichlid fish. (17th March 2020) - Vitt, Simon; Madge Pimentel, Iris; Thünken, Timo
Abstract: While the importance of kin discrimination, that is, kin recognition and subsequent differential treatment of kin and nonkin, is well established for kin-directed cooperation or altruism, the role of kin discrimination in the context of kin competition and kin avoidance is largely unexplored. Theory predicts that individuals avoiding competition with kin should be favored by natural selection due to indirect fitness benefits. Using an experimental approach, we investigated whether the presence of same-sex kin affects avoidance and explorative behavior in subadult Pelvicachromis taeniatus, a West African cichlid fish with strong intrasexual competition in both sexes. Pelvicachromis taeniatus is capable of recognizing kin using phenotype matching and shows kin discrimination in diverse contexts. When exposed to a same-sex conspecific, both males and females tended to interact less with the related opponent. Moreover, individuals explored a novel environment faster after exposure to kin than to nonkin. This effect was more pronounced in females. Individuals avoiding the proximity of same-sex relatives may reduce kin competition over resources such as mating partners or food. Abstract : Intrasexual competition between kin can decrease indirect fitness. We investigated whether the presence of a related same-sex competitor causes a change in explorative behavior compared with the presence of a nonkin competitor in the West African cichlid fish Pelvicachromis taeniatus . We observed less interaction with a related competitor and faster exploration of a novel environment when exposed to kin. Our results suggest that these cichlid fish try to avoid intrasexual competition with kin.